ETIKA SEKSUALITAS DALAM KASIH TUHAN: MENYELARASKAN RELASIPRIBADI DENGAN NILAI-NILAI KRISTIANI - Stefany Yosephine Edrika; Trifena Gratia; Elizama Gulo (CV. Denasya Smart Publisher, 2026)
Modern culture presents sexuality in a paradoxical manner: on the one hand, it is hypersexualized through media and the entertainment industry, while on the other hand, it remains silenced by moral taboos and a sense of shame. As a result, human sexuality is often understood reductively, either as a consumptive commodity or as a reality that must be suppressed. In this context, Christian ethics offers an alternative framework that views sexuality as an integral part of human dignity as creatures created by God. This article aims to explore the Christian theological vision of sexuality as a sacred, relational, and meaningful divine gift. Employing a biblical-theological approach from the Book of Genesis to the New Testament, this study examines the ontological foundations of sexuality as well as its unitive, procreative, and recreative purposes within God’s design. The article further analyzes the ethical implications of Christian sexuality in the contemporary world, particularly in relation to premarital relationships, pornography, and issues of homosexuality within church life. It is concluded that sexuality is not merely a biological function, but a language of self-giving that reflects the covenantal love between Christ and His Church, and therefore must be lived within the framework of holiness, love, and respect for human dignity.